Training process in Anaesthesiology and Intensive Care in Slovakia - Firment, Peter; Daňo, Andrej (Journal of the Portuguese Society of Anesthesiology, 2024)
Descreve-se no presente artigo o programa de formação em Anestesiologia e Medicina Intensiva na Eslováquia